How do hospitals address health inequalities experienced by children and young people: a grey literature scoping review protocol - Rachel Isba; Liz Brewster; Pallavi Patel; Louise Brennan; Judith Lunn; Fiona Egboko; Dora Pestotnik Stres (BMJ Open)
Introduction Health inequalities are unfair, systematic differences in health between people. In the UK, the Health and Social Care Act 2012 recognised health inequalities as a responsibility of the National Health Service (NHS). Health inequalities were foregrounded in the publication of 2019 NHS Long Term Plan and during the SARS-CoV-2/COVID-19 pandemic. Hospitals are well placed to address health inequalities through their role as anchor institutions. While many hospitals have begun to address inequalities, children are often overlooked or assumed to have the same needs as adult populations. This grey literature scoping review aims to identify, collate and present approaches taken by hospitals to address health inequalities in children and young people.Methods and analysis This scoping review will follow Joanna Briggs Institute guidance. A four-step approach to identifying grey literature will be used. Literature will be examined to identify approaches that aim to address health inequalities. Literature must describe the health inequality they aim to address and be initiated by the hospital. It will exclude literature not available in English and published before 2010. Two reviewers will independently review the results of the searches using the inclusion and exclusion criteria. Data will be extracted using a data extraction tool. Study findings will be presented in tabular form detailing the interventions identified.Dissemination The review will synthesise information on worldwide hospital approaches to addressing child health inequalities. The findings will be used to inform guidelines for children’s hospitals in the UK and will be disseminated through national and international professional bodies, conferences and research papers.